Espacio y sociedad. Reestructuración espacial de un antiguo enclave minero - Palomares León, Humberto (Frontera Norte, 2017)
Camilo Contreras Delgado, Tijuana, B.C., México, D.F., El Colegio de la Frontera Norte y Plaza y Valdés Editores, 2002, 191 pp.